Designing an Inclusive Digital Ecosystem for Public Services: A Framework for Accessibility Integration in Local Government Information Systems (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The digital transformation of public services has expanded rapidly across local governments, yet accessibility for people with disabilities remains insufficiently addressed. Many government websites fail to comply with international standards such as the Web Content Accessibility Guidelines (WCAG) 2.1, limiting equitable participation in e-government. This study aims to develop a conceptual model that integrates accessibility principles into the architecture of local government information systems. Using a framework construction approach, the research synthesizes findings from prior mixed-method evaluations involving accessibility audits and user perception surveys conducted in Kudus Regency, Indonesia. The resulting model, known as the Inclusive Digital Ecosystem Framework (IDEF), embeds the four WCAG 2.1 principles: Perceivable, Operable, Understandable, and Robust (POUR), into a multi-layered system architecture that spans interface design, application functionality, data management, and governance mechanisms. The study reveals that accessibility must evolve from a corrective process to a proactive design and governance culture. The IDEF framework demonstrates that technical compliance, user-centered design, and institutional policy can be systematically aligned to build sustainable, inclusive, and citizen-oriented digital ecosystems. This research contributes both theoretically and practically to the advancement of inclusive e-government by establishing a scalable model that links technological accessibility with policy accountability, supporting the realization of Sustainable Development Goals on equality and strong institutions.